Promoting Student's Reading Comprehension through Short Stories in ELT Classroom - Chusniawati, Tasriatul; Sibarani, Aura Dian; Rohmana, Wahyu Indah Mala (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study explores the impact of utilizing short stories to enhance students reading comprehension abilities in English Languange Teaching (ELT). Employing a qualitative approach through comprehensive interviews with three first-semester student, this study found that short stories not only enrich vocabulary and sentence structure, but also improves understanding of cultural context. The interview results showed that all participants showed high interest in short stories, with varied genre preferences, such as horror, culture, and fantasy. This research emphasizes the importance of selecting teaching materials that match students' interests to increase motivation and learning engagement. In addition, the integration of technology through interactive applications and digital media was also shown to increase students' reading interest. The findings suggest that the incorporation of short stories as an educational resource in English is not only effective in improving reading comprehension but also broadening students' cultural horizons, making it an attractive strategy in language learning. This study recommends that future teaching practices consider genre variation and technology integration to further enrich students' learning experience.